INTERACTION BETWEEN EDUCATION AND CULTURAL DIVERSITY: A LITERATURE REVIEW OF THE IMPLICATIONS of MULTICULTURALISM IN LEARNING CONTEXT - Siregar , Kardina Engelina (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Education plays an important role in facilitating integration between diverse cultures in an increasingly connected world. The aim of this research is to review previous literature that discusses the relationship between education and cultural diversity, as well as the implications of multiculturalism in the learning process. To increase understanding of the relationship between education and cultural diversity, the literature study method is used. These articles are collected from various academic sources and scientific journals. This research found that a multicultural approach is essential for designing inclusive curricula, teaching strategies, and learning environments. In addition, this research also emphasizes the difficulties and opportunities associated with implementing a multicultural approach in educational practice. This research emphasizes how these findings can impact changes in educational policies and learning methods that can increase understanding and appreciation of cultural diversity in an increasingly globalized society. Thus, this research helps us understand how education can help increase tolerance, mutual understanding, and appreciation for cultural diversity in the context of an increasingly globalized society.